Acylphenols and Dimeric Acylphenols from the Genus Myristica: A Review of Their Phytochemistry and Pharmacology - Muhamad Aqmal Othman; Yasodha Sivasothy (Plants, 2023)
The genus Myristica is a medicinally important genus belonging to the Myristicaceae. Traditional medicinal systems in Asia have employed plants from the genus Myristica to treat a variety of ailments. Acylphenols and dimeric acylphenols are a rare group of secondary metabolites, which, to date, have only been identified in the Myristicaceae, in particular, in the genus Myristica. The aim of the review would be to provide scientific evidence that the medicinal properties of the genus Myristica could be attributed to the acylphenols and dimeric acylphenols present in the various parts of its plants and highlight the potential in the development of the acylphenols and dimeric acylphenols as pharmaceutical products. SciFinder-n, Web of Science, Scopus, ScienceDirect, and PubMed were used to conduct the literature search between 2013–2022 on the phytochemistry and the pharmacology of acylphenols and dimeric acylphenols from the genus Myristica. The review discusses the distribution of the 25 acylphenols and dimeric acylphenols within the genus Myristica, their extraction, isolation, and characterization from the respective Myristica species, the structural similarities and differences within each group and between the different groups of the acylphenols and dimeric acylphenols, and their in vitro pharmacological activities.